SCIENCE TRENDS IN ISLAMIC BOARDING SCHOOLS AS AN EFFORT TO STRENGTHEN AQIDAH (RESEARCH STUDY AT IBAD AR-RAHMAN PANDEGLANG ISLAMIC BOARDING SCHOOL) - Humaeni (BAIK Publishers, 2025)
Islamic boarding schools are considered unresponsive to the times, difficult to accept change (renewal), while maintaining their traditional educational patterns (salafiyah) Islamic boarding schools become a kind of institution that tends to be exclusive and isolative from general social life. To respond to pesantren towards the modernization of Islamic education and socio-economic changes taking place in society. The Ibad Ar-Rahman Islamic Boarding School tries to answer this challenge by having a vision of realizing a generation of rabbanis who have a qur'ani spirit, armed with science and technology. The research method used in this research is phenomenological research with a qualitative approach. Phenomenological research is research on experiences, traditions and various cultural phenomena of a social community. The results of the research in this article, Ibad Ar-Rahman Islamic boarding school has a strong commitment to creating an interesting, structured learning climate, and is able to illustrate learning in everyday life. In addition, the learning program at the Ibad Ar-Rahman Islamic Boarding School is directed at students to be able to balance religion and science and reminds them that there is no conflict between the two. In accordance with the vision they have, namely the realization of a generation of rabbani who have a qur'ani spirit, armed with science and technology. So that the field of science is able to strengthen the creed of the students, not reduce their faith.